RANCANG BANGUN HEATER PADA BLOOD WARMER DENGAN TAMPILAN LCD BERBASISI MIKROKONTROLLER ATMega8535 - Flaviana Poprita Liuk Mau; Dzia Ur Ridha (JURNAL MUTIARA ELEKTROMEDIK, 2022)
Blood warmer is a tool that is used to warm blood in the process of blood transfusion. Inside the blood warmer there are several main parts that must be considered, the main part that must be considered is the heater part. With the main aim to maintain the temperature in the blood cantomate so that no clotting occurs. The design of this tool aims to obtain the design of blood builder using the LM35 sensor as a temperature indicator to be displayed on the LCD. This research starts from the stages of collecting various sources, gathering information designing tool products, designing and perfoming function tests. Device hard covening design circuit supply power, circuit minumum system ATMega8535 microcontroller, a temperature sensor circuit. circuit,heater driver circuit LCD. While design for device soft covering programming basic language complier. Principle work from system on a whole namely : temperature sensor circuit will give input on the microcontrller for processed and produce output in the fom of hot via heater